Psalm 27:4 – To reflect in his temple: Communion with YHWH as the culmination of the journey of life - Botha, Philippus J. (HTS teologiese studies, 2021)
Since the time of Mowinckel, the verb בקר (pi) in Psalm 27:4 was often interpreted as referring to a priest’s function of examining an offering. The parallel part of the verse and other intratextual and intertextual considerations render this interpretation of the verb improbable. The context of the psalm and the cluster of Psalms 25–34, as well as parallels Psalm 27 has with Psalm 23, suggest that the verb בקר refers to reflection on the privilege of being in YHWH’s presence. The enjoyment of such communion with YHWH, which includes the study of his Torah, is portrayed as the culmination of the journey of life in Psalms 25–34. The author argues that this is also hinted at in Psalm 27.Contribution: The contribution of this article towards the focus of HTS as “Historical Thought and Source Interpretation” centered around its use of the literary context of a psalm to question the notion of a reconstructed cultic setting as the only possible hermeneutical key to interpret Psalm 27.